Research and practice working together in the Loimijoki project - Luostarinen, Matti (gb, 1998)
The Loimijoki project is a multidisciplinary research and development project in the environment of the home river of MTT (Agricultural Research Centre) and the regional "test laboratory". The research is associatedwith integrated natural sciences and basic research in the humanities and with its transfer mechanisms when looking for solutions for environmental and biological, economic, social and technological problems in the environmental issues of agriculture. The project has producted, for example,the Agropolis sciensce park and a second generation strategy for science parks, the Agri demonstration park for agricultural research, the Agronet information service and a national innovation centre for food economy. In addition, dozens of demonstration projects drawing mainly from the biological research and applications of the various sciences developing the rural community are active along the river.
Keywords: Ys; jokiverkosto; jokiprojekti; integraatio; johtaminen; projektiorganisaatio; rivers network; integrating systems; river projects; leadership; project organisation; strategy; activity